The Scottish Independence Movement: National or Nationalist? - Nathalie Duclos (Revue LISA)
Focusing on the case of the Scottish independence movement, this article aims to reflect on whether support for independence necessarily equates to nationalism. The reflection hinges on two premises: first, independence does not hold the same importance for all pro-independence actors, and second, many of them have chosen to put a rejection of nationalism at the heart of their case for independence. The article argues in favour of dividing pro-independence actors into two groups: nationalists for whom the pursuit of self-government is not only a means to other ends, but also an end goal to be achieved on the basis of nationalist principles; and non-nationalists for whom independence is only ever presented as a means to other, greater ends. The article suggests that rather than a nationalist movement, the Scottish independence movement is perhaps best described as a “national” movement, i.e. a Scottish-wide coalition of actors united in their support for independence, but divided over the place they give to independence in their order of priorities, the arguments used to defend it, as well as their perception of nationalism as a belief-system.